Brentuximab vedotin as monotherapy for unresectable breast implant‐associated anaplastic large cell lymphoma. Issue 5 (11th April 2019) - Stack, Anthony; Levy, Isaac
Key Clinical Message: BI‐ALCL is a rare CD30+ T‐cell malignancy, which is known to complicate textured breast implants. The CD30‐targeting immunoconjugate, brentuximab vedotin, has been suggested for invasive BI‐ALCL; however, its efficacy for unresectable BI‐ALCL has not been demonstrated. We present a case of unresectable BI‐ALCL, which was successfully treated with brentuximab vedotin. Abstract : BI‐ALCL is a rare CD30+ T‐cell malignancy, which is known to complicate textured breast implants. The CD30‐targeting immunoconjugate, brentuximab vedotin, has been suggested for invasive BI‐ALCL; however, its efficacy for unresectable BI‐ALCL has not been demonstrated. We present a case of unresectable BI‐ALCL, which was successfully treated with brentuximab vedotin.